Descobrimento ou encobrimento: como o youtube mostra os indígenas no momento da chegada dos portugueses - Rosa, Éderson Gaike da (2017)
This work tries to make an analysis of the teaching of history in the times of Internet, when we perceive that more and more the students look for knowledge and information in the world - wide network of computers. Within this reality, we sought to know about the use of videos hosted on the Youtube site that presented the theme related to what many call "discovery of Brazil", that is, the arrival of the Portuguese in our territory and all its unfolding. The main idea is to understand if there is a diffusion of the new concepts of historiography, which problematize the question of "discovery", understanding that this concept is eurocentric and covers a vast pre-existing culture upon arrival in Portugal. Also, we try to evaluate if the digital means of the world-wide network of computers and, in particular, Youtube has been able to follow in general way the needs of the historiography and the teaching of history, that, even under the law has resignificado our history and given More voice to the peoples and formative cultures of our nation than not only Europeans